2017
DOI: 10.5194/aab-60-51-2017
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide QTL mapping results for regional DXA body composition and bone mineral density traits in pigs

Abstract: Abstract. In a previous study, genome-wide mapping of quantitative trait loci (QTL) for five body composition traits, three bone mineral traits and live weight was performed using whole-body dual-energy X-ray absorptiometry (DXA) data. Since QTL for bone mineral traits were rare, the current study aimed to clarify whether the mapping results were influenced by the analysed body regions. Thus, the same material (551 pigs) and methods as in the whole-body QTL mapping study were used. However, for evaluation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 48 publications
(69 reference statements)
0
13
0
Order By: Relevance
“…Monogastric animal species appeared to have DNA variations contributing to the phenotypic variability of certain P characteristics such as P utilization [27,[61][62][63] and bone mineralization [64,65]. In chicken and quail populations, estimations have shown a considerable heritability of approximately 10% [62,63,66].…”
Section: Animal Geneticsmentioning
confidence: 99%
“…Monogastric animal species appeared to have DNA variations contributing to the phenotypic variability of certain P characteristics such as P utilization [27,[61][62][63] and bone mineralization [64,65]. In chicken and quail populations, estimations have shown a considerable heritability of approximately 10% [62,63,66].…”
Section: Animal Geneticsmentioning
confidence: 99%
“…Indeed, skeletal disorders such as rickets and osteochondrosis occur in both young piglets with rapidly growing bones and adult pigs, resulting in lameness and culling and thus in economic losses (Stern et al 1995 ; Fukawa and Kusuhara 2001 ). Moreover, bone mineralization is correlated with body weight and body composition (Rothammer et al 2017 ). The bone consists of the protective cortical and the metabolic active trabecular bone, being also the reservoir for calcium (Ca) and phosphorus (P).…”
Section: Introductionmentioning
confidence: 99%
“…DXA showed differences in bone mineralization in pigs, especially pronounced for different body regions and among male sex types. For further studies, it is necessary to evaluate whether a lower or higher BMC or BMD affects the health of male fattening pigs, as has been published in human medicine, where a declining bone mineral density is a surrogate for declining bone strength (Ryan, 1997;Bonnick, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Recently published genome-wide association studies by Rothammer et al (2014Rothammer et al ( , 2017 showed that further candidate genes or gene regions were found for whole-body or regional bone mineral traits assessed by using DXA in pigs in vivo. Therefore, genomic analysis and additional BMC or BMD phenotypes can add information in terms of leg health and animal welfare in pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation